Simulasi dan Eksperimental Isothermal Aliran Eksternal Resirkulasi pada Up-Draft Gasifier - Fajri Vidian; Hery Prabowo; Yulianto .; Adi Surjosatyo; Yulianto Sulistyo Nugroho (Jurnal Teknik Mesin (Sinta 3), 2011)
Gasification process at updraft gasifier produces greater amount of tar than other type of gasifier. To reduce tar at updraft gasifier, the pirolysis gas will be re-circulated to combustion zone and to exhaust gas from reduction zone. Recirculation of pirolysis gas to combustion zone can be carried out by using ejector. Ejector is an equipment used to inject the secondary fluid flow by the movement of momentum and energy from high speed primary flow (jet). The research conducted with isothermal 3D simulation using CFD and experimental investigation of recirculation flow using ejector at updraft gasifier. Ejector velocity for simulation and experimentation is constant at 0.6 m/s. Ejector’s nozzle exit position (NXP) direction will be varied. The goal of this research is to obtain information of optimal nozzle exit position for producing maximum velocity of gas recirculation. The result of simulation and experiment shows that the change of nozzle exit position direction to – x axis from zero point, it will give maximum velocity of gas recirculation flow with the optimum position of nozzle exit position at the range of -3 to -4 cm from zero point.